Exploring the Effect of AI-Driven Contextual Conversations on EFL Grammar Learning at University Level in Saudi Arabia - Mohammed , Ghazwan Mohammed Saeed; Ja’ashan , Mohammed Mohammed Nasser Hassan (Journal of Ecohumanism, 2025)
This study aims to explore EFL grammar learning through AI-driven contextual conversations at the university level in Arab countries, particularly in Saudi Arabia. To achieve the objectives of the study, 110 students who are enrolled at University of Bisha, Saudi Arabia, participated in this study. Quantitative and qualitative methods were used to collect the data of the study. The participants sat for a pre-test and a post-test, and they participated in filling in a questionnaire that was designed for the purpose. The findings of the study showed that there was an improvement in the post-test after the students used an AI tool for learning English grammar through contextual conversations. The findings of the study also showed that AI is engaging and enjoyable in learning English grammar. The AI tool that the students used enhanced the students’ motivation and confidence to learn grammar. The students found that the feedback of the AI tool was clear, constructive, and highly beneficial for learning grammar. It showed that learning grammar by AI tool is more effective as it is used in realistic contexts. Its ease of use was another key factor that helped the students focus on learning without technical barriers. The students’ preference for the AI tool over traditional methods suggests that the grammar instruction could benefit significantly from AI integration. The study ended with some recommendations that would certainly benefit the EFL learners, instructors and syllabi makers and enhance the learning environment. Some pedagogical implications are also included accordingly.